2006
DOI: 10.1364/oe.14.010403
|View full text |Cite
|
Sign up to set email alerts
|

Accurate lattice extraction in integral images

Abstract: Integral imaging is one of the most promising techniques for delivering three-dimensional content. Most processing tasks usually require prior knowledge of the size and positions of the elemental images that comprise an integral image. In this paper we propose an automated method for calibrating the acquisition setup, by applying a preprocessing stage to an acquired integral image. The skew angle is extracted and the size and positions of the elemental images are accurately determined. For these purposes a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…The two main research topics have been to overcome the physical limitations and to search for new applications of integral imaging systems. For solving the physical limitations, several researchers have proposed solutions to the pseudoscopic problem [63][64][65][66], to the uncertainty in the position and angle of the microlenses and the elemental images with respect to the sensor [67][68][69][70], and to the limitation of the viewing angle [71][72][73][74]. Solutions to the limited depth of field [75][76][77] or to the detrimental effect of the facet braiding have also been proposed [78,79].…”
Section: The Viewer Sees Point S Closer To Him Than the Other Pointmentioning
confidence: 99%
“…The two main research topics have been to overcome the physical limitations and to search for new applications of integral imaging systems. For solving the physical limitations, several researchers have proposed solutions to the pseudoscopic problem [63][64][65][66], to the uncertainty in the position and angle of the microlenses and the elemental images with respect to the sensor [67][68][69][70], and to the limitation of the viewing angle [71][72][73][74]. Solutions to the limited depth of field [75][76][77] or to the detrimental effect of the facet braiding have also been proposed [78,79].…”
Section: The Viewer Sees Point S Closer To Him Than the Other Pointmentioning
confidence: 99%
“…Among the possible applications are analyzing regions, image cells, and image mixing; designing autostereoscopic displays (full-parallax and HPO displays with rectangular, hexagonal, and slanted image cells); measurement, analysis, simulation, and control of the geometric characteristics of 3D displays [35,56]; and analyzing the depth and resolution [26]. There can be many other applications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…All these methods detect and register grid lines and using this metric information transformation matrices are formed that are subsequently applied in the correction procedure. In [7] a method based on the Hough transform was shown that estimated rotation, position and size information for EIs using square lenses. A perspective rectification method also utilizing the Hough transform was shown in [8].…”
Section: Introductionmentioning
confidence: 99%